A comprehensive mixed-methods study on cross-border e-commerce SMEs, digital transformation and dynamic managerial capabilities - Yao, Guannan; Dato’ Mansor, Zuraina; Ghazali, Hazrina; Yan, Zhen (Asia Pacific Academy of Science Pte Ltd, 2024)
The development of the digital trade ecosystem heavily relies on the expansion of cross-border e-commerce (CBEC) platforms. CBEC companies are actively involved in digital transformation (DT) initiatives to bolster their core competencies and market share. E-commerce has experienced rapid growth in recent years, particularly since the global market faced significant disruptions due to the COVID-19 pandemic in 2020. As the market continues to globalize, more Chinese entrepreneurs are shifting their focus towards the international arena. They aim to increase investments in high-tech productivity within their organizations while also concentrating on enhancing their dynamic managerial capabilities to drive transformation within cross-border e-commerce companies. Therefore, the current study examines how organizational DT impacts the management capabilities of Chinese cross-border e-commerce managers from the perspective of dynamic managerial capabilities. The research employed a mixed-method approach. Firstly, a bibliometric analysis was conducted using VOS Viewer and R studio. Data was collected from two databases, Web of Science and Scopus, to analyze publication trends across countries and identify journals with the highest number of publications and citations. This analysis aimed to provide a comprehensive understanding of the context of the subject. Secondly, seven in-depth interviews were conducted using purposive and chain-referral sampling techniques, drawing insights from CEOs based on their real-life experiences with organizational DT. The results of the study revealed that technology has led to the decentralization and flattening of organizational structures. Managers are increasingly using social platforms to connect with experts and potential collaborators. Furthermore, the study highlights the role of psychological support in bolstering dynamic managerial capabilities.